Importancia en el cumplimiento del Código de Ética para el ejercicio de la profesión como Auditor hacia la correcta ejecución de Las Normas Internacionales de la Auditoría. (2022)
In Colombia, companies are immersed in multiple policies for the constitution and legal monitoring of them and thus opt for the good management of an economy that is sustainable and profitable that in turn provides reliability and veracity in what is contemplated. However, the Central Board of Accountants normalizes the code of ethics of the public accountant in Law 43 of 1990 compiled in Decree 0302 of 2015. In the process of convergence to international auditing standards (ISAs) and so on. In the internalization of accounting, there is a presumption of taking into account the standards of IFAC's code of ethics and international conduct, as a global normative basis for the presentation of financial information. Inspired by the importance of the applicability of these and that the figure of the auditor is competent to exercise his role, in which he must have ethical principles, independence, professional skepticism and professional judgment. For this, the main objective of this work is to investigate three specific topics, in which the importance of the International Auditing Standards, the Code of Ethics (IFAC) and the role of the Auditor are highlighted. In addition, with this research it was decided to carry out a qualitative and descriptive work, allowing to deepen the ideas, involving a great interpretative richness since primary sources were used for data collection, such as personal interviews with professionals from their perspective. and your professional experience; seeking to obtain different views and thus enrich this research